Tanggung Jawab Sosial Perusahaan (CSR) Dalam Perspektif Regulasi (Studi: Indonesia, Belanda dan Kanada) - Siti Maryama (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2013)
This article aims to understand the concept of CSR is implemented in many countries, particularly Indonesia, the Netherlands and Canada. Although these countries do not have the specific regulations governing the application of CSR by companies, but the They positioned CSR as an obligation to do. CSR in Indonesia is set in some of the rules, such as the limited liability laws, state laws, laws on investment, and is regulated in others. While in the Netherlands is set in CSR Netherlands. While in Canada formed CBSR (Canadian Business for Social Responsibility) as the government's commitment to the importance of CSR. From the concept of CSR undertaken by these countries, CSR has the same goal of good relations between companies, communities, and the environment.